Resin composition for anti-slip mat and method for producing the same, and anti-slip mat and method for producing the same

By using a synthetic resin composition of barium sulfate and thermoplastic elastomer, combined with optimized particle size and proportion, the problems of low productivity and insufficient wear resistance in the manufacturing process of existing anti-slip pads are solved, and self-salting and high in water are achieved Abrasion resistance effect.

CN116157467BActive Publication Date: 2025-02-21ARONKASEI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180051760.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-14
Filing Date
2021-11-26
Publication Date
2025-02-21
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The existing anti-slip pads require a sulfurization process during the manufacturing process, which has low productivity and is difficult to achieve the effect of self-salting and high wear resistance in water.

Method used

By adjusting the particle size and content of barium sulfate, an olefin resin and a softener are used to form a large amount of resin composition with excellent specific gravity, mechanical strength and wear resistance by adjusting the particle size and content of barium sulfate. And manufactured by a continuous mixer.

Benefits of technology

The anti-slip pad is realized to self-sink in water and is not easily deviated, has high mechanical strength and wear resistance, improves productivity, and can effectively prevent slipping in slippery environments such as bathrooms and bathtubs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004089759440000281
    Figure BDA0004089759440000281
  • Figure BDA0004089759440000291
    Figure BDA0004089759440000291
  • Figure BDA0004089759440000301
    Figure BDA0004089759440000301
Patent Text Reader

Abstract

The resin composition for anti-skid mats of the present invention has synthetic barium sulfate and a thermoplastic elastomer composition as essential components, contains 20 to 70% by mass of the synthetic barium sulfate, and has a type A durometer hardness of 20 to 80. By using the resin composition of the present invention, an anti-skid mat that can be used in water can be easily manufactured, and the anti-skid mat is not only soft and can sink in water, but also easy to handle by the elderly, etc., is lightweight, and is excellent in mechanical strength and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for an anti-slip mat, and also to a method for producing the resin composition for an anti-slip mat. Furthermore, the present invention relates to an anti-slip mat, and also to a method for producing the anti-slip mat. Background Art

[0002] Anti-skid mats used around water are widely used in order to prevent falls on the edge of a pool (swimming pool, pool, bathtub, etc.), on the bottom of a pool, on the floor of a bathroom, in a bathtub, on the floor of a toilet, etc. In particular, since elderly people often fall and get injured in bathtubs, it is known to prevent falls by sinking the anti-skid mat into the bottom of a bathtub.

[0003] The resin composition used for the anti-slip mat needs to have a specific gravity greater than that of water, be difficult to deflect, and not easily slide even when stepped on or sat on. Furthermore, it is required to have sufficient strength and wear resistance to withstand practical use, and softness to obtain a sense of comfort. In addition, sometimes, chlorine water resistance to withstand the chlorine contained in tap water is also required. In addition, in terms of economy, good productivity is required in order to suppress costs, and in terms of environment, a recyclable material for reducing environmental load is required.

[0004] The above-mentioned anti-slip mat uses a soft material such as rubber, and the anti-slip function is exerted by the friction effect of the soft material. Therefore, by increasing the specific gravity of the soft material, the slip between the mat and the floor surface can be prevented even in a wet environment. In addition, mechanical strength such as not being damaged by people stepping on or sitting on it, and wear resistance for preventing wear caused by repeated use are required. In addition, in order to obtain comfort when sitting, moderate softness is required.

[0005] Conventionally, soft materials used for anti-slip mats have to be cross-linked to achieve strength and wear resistance, requiring a vulcanization step. In addition, they are produced by batch production based on compression molding, which has the problem of low productivity.

[0006] Patent Document 1 proposes a composition for an anti-slip mat containing a styrene-based elastomer, a polypropylene resin, a rubber softener, and calcium carbonate.

[0007] In this method, there is no anti-slip mat enclosed in water, especially in water, and since the specific gravity of the composition itself is low, there is a disadvantage that the anti-slip effect is insufficient in a wet environment. Furthermore, when the composition is used alone, the strength during use is insufficient, so the resin needs to be welded to the base resin, and the manufacturing process is complicated.

[0008] Patent Document 2 proposes a method of adding a large amount of high-specific-gravity barium sulfate to synthetic rubber or natural rubber, further embossing the rubber for anti-slipping, and then vulcanizing the rubber.

[0009] In this method, since the melt viscosity of the composition when the composition is mixed is high, it is necessary to use a batch roll kneading machine, and further there are disadvantages such as complicated production process and low productivity.

[0010] Patent Document 3 proposes a composition of a highly filled styrene elastomer, a thermoplastic resin, a rubber softener, and heavy calcium carbonate or barium sulfate in order to increase the specific gravity of the styrene elastomer and improve the sound insulation properties.

[0011] In this method, the breaking strength is high, but the breaking elongation is low, and the mechanical strength as an anti-slip mat is insufficient. Furthermore, due to the high melt viscosity, a complicated manufacturing method is required, which is to use a batch mixer to prepare the composition, a roll forming machine to form a sheet, and then a compression molding machine to obtain a product, so the productivity is low.

[0012] In addition, Patent Document 4 proposes an anti-slip sheet containing a thermoplastic elastomer or rubber and an inorganic filler.

[0013] In this method, since the focus is too much on sinking in water, the specific gravity of the sheet is as high as 2.2 or more, which makes it difficult for the elderly, who have increased in number with the development of an aging society in recent years, and infants and children who help with housework (hereinafter, the elderly, infants, and children are collectively referred to as "elderly people, etc.") to handle. Furthermore, although the bathtub mat has sufficient softness, anti-slip effect, and specific gravity for use in water, as a product structure, the three-layer structure of the surface layer / high specific gravity middle layer / back layer is used to supplement each function, resulting in a complicated manufacturing process and low productivity.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Laid-Open No. 10-279747

[0017] Patent Document 2: Japanese Patent Application Laid-Open No. 10-215911

[0018] Patent Document 3: Japanese Patent Application Laid-Open No. 62-256845

[0019] Patent Document 4: Japanese Patent Application Publication No. 2001-181408 Summary of the invention

[0020] Problems to be solved by the invention

[0021] As described above, conventionally known anti-slip mats have problems in production, namely, a vulcanization step of a raw material composition is required, the material cannot be recycled from the molded product, and the productivity is low due to batch production.

[0022] The present invention aims to provide a resin composition for obtaining an anti-slip mat and a method for producing the same, as well as an anti-slip mat and a method for producing the same, wherein the anti-slip mat has excellent moldability, a specific gravity that is easy to handle, excellent wear resistance, can sink in water, and exhibits an anti-slip effect when placed on the mat.

[0023] Means of solving problems

[0024] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that when synthetic barium sulfate is used in barium sulfate, the strength and wear resistance are significantly improved compared with the case of using natural barium sulfate (bumpy barium sulfate). Therefore, it is found that if a resin composition containing a specific thermoplastic elastomer and synthetic barium sulfate and having a certain range of A-type durometer hardness is used, it has an optimal specific gravity, a good balance between tensile strength and elongation, a high anti-slip effect, and excellent wear resistance, thereby completing the present invention.

[0025] Furthermore, the inventors have found that by using a specific amount of a mildew-proofing agent in a resin composition, the formation of mildew can be suppressed even when the obtained anti-slip mat is used in a place with water, particularly in a bathroom or a bathtub.

[0026] The present invention provides the following means.

[0027] [1] A resin composition for an anti-slip mat, characterized in that it contains synthetic barium sulfate and a thermoplastic elastomer composition as essential components, contains 20 to 70% by mass of the synthetic barium sulfate, and has a type A durometer hardness of 20 to 80.

[0028] [2] The resin composition for an anti-slip mat according to [1] above, wherein the thermoplastic elastomer composition comprises a thermoplastic elastomer component (A), an olefin resin component (B) and a softener component (C),

[0029] The olefin resin component (B) is contained in a ratio of 10 to 90 parts by mass, and the softener component (C) is contained in a ratio of 100 to 300 parts by mass, based on 100 parts by mass of the thermoplastic elastomer component (A).

[0030] [3] The resin composition for an anti-slip mat according to [2] above, wherein the thermoplastic elastomer component (A) is at least one selected from the group consisting of styrene-based elastomers, olefin-based elastomers, and hydrogenated styrene-based elastomers.

[0031] [4] The resin composition for an anti-slip mat according to [2] or [3] above, wherein the olefin-based resin component (B) is a polypropylene resin.

[0032] [5] The resin composition for an anti-slip mat according to any one of [2] to [4] above, wherein the softener component (C) is paraffin oil.

[0033] [6] The resin composition for an anti-slip mat according to any one of [1] to [5] above, wherein the elastomer composition further contains a mildew-proofing agent, and the content of the mildew-proofing agent is 0.01 to 10 parts by mass relative to 100 parts by mass of the thermoplastic elastomer component (A).

[0034] [7] An anti-slip mat, characterized in that it is a molded product of the resin composition for an anti-slip mat according to any one of [1] to [6] above, contains 20 to 70% by mass of synthetic barium sulfate, and has a type A durometer hardness of 20 to 80.

[0035] [8] The anti-slip mat according to [7] above, wherein the specific gravity of the molded article is greater than 1.0 and less than 2.2.

[0036] [9] The method for producing a resin composition for an anti-slip mat according to any one of [1] to [6], which comprises a kneading step using a continuous kneading machine.

[0037]

[10] The method for producing an anti-slip mat according to [7] or [8], wherein the resin composition for an anti-slip mat according to any one of [1] to [6] is subjected to injection molding.

[0038] Effects of the Invention

[0039] The resin composition for anti-slip mats of the present invention has a high specific gravity and can sink in water. Moreover, the anti-slip mats do not become too heavy, so that the elderly and the like will not injure their backs and legs and are easy to handle.

[0040] Furthermore, the resin composition for an anti-slip mat of the present invention has excellent moldability, and thus can produce an anti-slip mat with high productivity that has good softness for use, mechanical strength to withstand people stepping on or sitting on it, and excellent wear resistance.

[0041] The resin composition for anti-slip mats of the present invention has good fluidity and can be produced by a continuous kneading machine such as an extruder. In addition, the resin composition for anti-slip mats of the present invention is suitable for injection molding, so the productivity of the anti-slip mat is excellent. The resin composition for anti-slip mats of the present invention is a thermoplastic composition, so the material can be recycled from the molded product.

[0042] The anti-skid mat of the present invention can be easily operated by the elderly and the like without causing any accidents, and can be easily installed at a desired position by simply sinking it into water. In addition, it can be easily installed even in a place where it is difficult to attach a suction cup. In addition, it has excellent friction resistance and can be used for a long time. Furthermore, the anti-skid mat of the present invention can be manufactured by injection molding, and has high productivity.

[0043] The anti-slip mat obtained from the anti-slip mat resin composition of the present invention has excellent mechanical strength and wear resistance, and is therefore suitable for use in bathrooms and bathtubs. In addition, the anti-slip mat of the present invention can be used not only in bathrooms and bathtubs, but also as a fall prevention mat in water-soaked environments such as poolsides and bus hatches. DETAILED DESCRIPTION

[0044] Hereinafter, the present invention will be described in detail.

[0045] The resin composition for an anti-slip mat of the present invention (hereinafter also referred to as "resin composition") contains synthetic barium sulfate and a thermoplastic elastomer composition as essential components and has a type A durometer hardness of 20 to 80.

[0046] In the present invention, the thermoplastic elastomer composition preferably contains a thermoplastic elastomer component (A), an olefin-based resin component (B), and a softener component (C).

[0047] That is, the resin composition of the present invention is preferably a resin composition comprising synthetic barium sulfate, a thermoplastic elastomer component (A), an olefin resin component (B) and a softener component (C). In addition, the resin composition of the present invention preferably further comprises a mildew preventer.

[0048] Barium sulfate is roughly divided into synthetic barium sulfate and natural barium sulfate (also called dusty barium sulfate or barite powder) according to its production method, but synthetic barium sulfate is used in the present invention.

[0049] The particle size of the synthetic barium sulfate used in the present invention affects the flexibility, strength, wear resistance and fluidity during injection molding, so it is preferably in the following particle size range. Specifically, the particle size of 10% under the cumulative distribution sieve on a volume basis (hereinafter referred to as "particle size D10") is preferably 0.01 to 5 μm. It is more preferably 0.05 to 3 μm, further preferably 0.1 to 2 μm, and particularly preferably 0.2 to 1 μm. When the particle size D10 is less than 0.01 μm, the anti-slip pad obtained becomes hard, the feel of use deteriorates, or the fluidity of the resin composition deteriorates, and it is sometimes difficult to manufacture by injection molding. When the particle size D10 is greater than 5 μm, the strength and wear resistance of the anti-slip pad obtained are sometimes reduced.

[0050] In addition, the particle size of 50% of the cumulative distribution under the sieve on a volume basis (hereinafter referred to as "particle size D50" or "median particle size") is preferably 0.05 to 30 μm. It is more preferably 0.07 to 25 μm, further preferably 0.1 to 20 μm, further preferably 0.1 to 15 μm, particularly preferably 0.15 to 10 μm, and more particularly preferably 0.15 to 6 μm. When the particle size D50 is less than 0.05 μm, the resulting anti-slip pad becomes hard, the feel of use deteriorates, or the fluidity of the resin composition deteriorates, and it is sometimes difficult to manufacture by injection molding. When the particle size D50 is greater than 30 μm, the strength and wear resistance of the resulting anti-slip pad are sometimes reduced.

[0051] Furthermore, the volume-based cumulative distribution undersize sieve 90% (hereinafter referred to as "particle size D90") is preferably 0.1 to 50 μm. It is more preferably 0.3 to 40 μm, further preferably 0.4 to 30 μm, and particularly preferably 0.5 to 20 μm. When the particle size D90 is less than 0.1 μm, the obtained anti-slip mat becomes hard, the feel of use deteriorates, or the fluidity of the resin composition deteriorates, and it is sometimes difficult to manufacture by injection molding. When the particle size D90 is greater than 20 μm, the strength and wear resistance of the obtained anti-slip mat are sometimes reduced.

[0052] From the viewpoint of good balance of the softness, strength and fluidity of the resin composition during injection molding, the difference between the particle size D10 and the particle size D90 is as small as possible, and the difference between the particle size D90 and the particle size D10 (particle size D90-particle size D10) is preferably 20 μm or less, more preferably 10 μm or less, further preferably 2 μm or less, further preferably 1.5 μm or less, and particularly preferably 1 μm or less.

[0053] In addition, the said particle diameter can be measured using the particle diameter / particle size distribution measuring apparatus.

[0054] In order to improve the dispersibility in the resin composition, the synthetic barium sulfate may be surface treated.

[0055] Examples of the surface treatment agent include coupling agents such as silane coupling agents and titanate coupling agents; and organic compounds containing polar groups such as carboxyl groups, amino groups, epoxy groups, isocyanate groups, and hydroxyl groups (hereinafter referred to as "polar group-containing organic compounds").

[0056] Examples of the silane coupling agent include:

[0057] Vinyl trichlorosilane, vinyl triethoxysilane, vinyl-tri(β-methoxyethoxy)silane and other vinyl-containing silane coupling agents;

[0058] Silane coupling agents containing epoxy groups such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane;

[0059] Silane coupling agents containing methacryl or acryl groups, such as 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, and 3-acryloxypropyltrimethoxysilane;

[0060] Amino-containing silane coupling agents such as N-2-(aminoethyl)-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltrimethoxysilane;

[0061] Silane coupling agents containing isocyanate groups such as 3-isocyanatepropyltriethoxysilane;

[0062] Silane coupling agents containing isocyanurate groups such as tris(trimethoxysilylpropyl)isocyanurate;

[0063] Silane coupling agents containing urea groups such as 3-ureapropyltrimethoxysilane;

[0064] Silane coupling agents containing styrene groups such as p-styrene trimethoxy silane;

[0065] Halogen-containing silane coupling agents such as 3-chloropropyltrimethoxysilane;

[0066] Silane coupling agents containing mercapto groups, such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane.

[0067] Examples of the titanate coupling agent include tetraisopropyl titanate, tetra-n-butyl titanate, tetraoctyl titanate, butyl titanate dimer, isopropyl triisostearate titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl-tri(dioctyl pyrophosphate) titanate, and bis(dioctyl pyrophosphate) ethylene titanate.

[0068] Examples of the polar group-containing organic compound include:

[0069] Aliphatic organic compounds containing carboxyl groups such as oleic acid, lauric acid, and stearic acid;

[0070] Aliphatic organic compounds containing amine groups, such as oleylamine, laurylamine, and stearylamine;

[0071] Aliphatic compounds containing epoxy groups such as oleyl glycidyl ether, lauryl glycidyl ether, and stearyl glycidyl ether, and aliphatic organic compounds containing isocyanate groups such as oleyl isocyanate, lauryl isocyanate, and stearyl isocyanate;

[0072] Hydroxyl-containing aliphatic organic compounds such as oleyl alcohol, lauryl alcohol, stearyl alcohol, etc.

[0073] From the viewpoints of compatibility and miscibility with the thermoplastic elastomer composition, strength and wear resistance of the resin composition of the present invention, the surface treatment agent is preferably a carboxyl group-containing aliphatic organic compound such as stearic acid or an amino group-containing aliphatic organic compound such as stearylamine.

[0074] When the resin composition containing the surface-treated synthetic barium sulfate is prepared by kneading, the synthetic barium sulfate, the surface treatment agent, the thermoplastic elastomer component (A), the olefin resin component (B), and the softener component (C) which are raw material components of the thermoplastic elastomer composition may be simultaneously introduced into a kneader and mixed. Alternatively, the synthetic barium sulfate treated in advance with the surface treatment agent may be used together with the thermoplastic elastomer component (A), the olefin resin component (B), and the softener component (C).

[0075] From the viewpoint of the wear resistance of the resin composition of the present invention, with barium sulfate as 100 parts by mass, the above-mentioned surface treatment agent can be used in the range of more than 0.01 parts by mass and less than 80 parts by mass. From the viewpoint of compatibility and miscibility with the resin composition of the present invention, the lower limit is preferably more than 0.03 parts by mass, more preferably more than 0.05 parts by mass, more preferably more than 0.07 parts by mass, and particularly preferably more than 0.1 parts by mass. On the other hand, from the viewpoint of the strength and wear resistance of the anti-slip mat obtained, the upper limit is preferably less than 60 parts by mass, more preferably less than 40 parts by mass, more preferably less than 30 parts by mass, and particularly preferably less than 10 parts by mass.

[0076] Synthetic barium sulfate not only improves wear resistance, but also has the effect of increasing the specific gravity of the resin composition of the present invention. Therefore, when the resin composition as a whole is set to 100 mass%, the amount of synthetic barium sulfate used is 20 to 70 mass%. When it is less than 20 mass%, the specific gravity of the resin composition of the present invention is small and cannot sink in water. When it is greater than 70 mass%, the obtained anti-slip mat becomes heavy, which causes a burden on the user's handling.

[0077] It is preferably 30 to 70 mass %, more preferably 40 to 70 mass %, and even more preferably 50 to 70 mass %.

[0078] The thermoplastic elastomer composition of the present invention preferably comprises a thermoplastic elastomer component (A), an olefin-based resin component (B) and a softener component (C).

[0079] [Thermoplastic elastomer component (A)]

[0080] The thermoplastic elastomer component (A) used in the present invention is not particularly limited as long as it is composed of a thermoplastic elastomer.

[0081] Examples of the thermoplastic elastomer include olefin elastomers, styrene elastomers, hydrogenated styrene elastomers, vinyl chloride elastomers, chlorinated polyethylene elastomers, ethylene-vinyl acetate elastomers, 1,2-polybutadiene elastomers, polyurethane elastomers, polyester elastomers, polyamide elastomers, and fluorine-based elastomers.

[0082] From the viewpoint of the water resistance and anti-slip effect of the obtained anti-slip mat, olefin-based elastomers, styrene-based elastomers, hydrogenated styrene-based elastomers, vinyl chloride-based elastomers, and chlorinated polyethylene-based elastomers are preferred.

[0083] Furthermore, from the viewpoint of the flexibility, strength and abrasion resistance of the anti-slip mat obtained when highly filled with barium sulfate, olefin-based elastomers, styrene-based elastomers and hydrogenated styrene-based elastomers are more preferred, and from the viewpoint of chlorine water resistance, styrene-based elastomers and hydrogenated styrene-based elastomers are particularly preferred.

[0084] The above-mentioned olefin-based elastomer is preferably a copolymer containing ethylene units or propylene units. For example, ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, propylene-1-butene copolymer, propylene-1-hexene copolymer, propylene-1-octene copolymer, ethylene-propylene-1-butene copolymer, ethylene-propylene-1-hexene copolymer, ethylene-propylene-1-octene copolymer, ethylene-propylene-diene copolymer, etc. can be mentioned. Among them, ethylene-α-olefin copolymers containing ethylene units and structural units from α-olefins are preferably included. In addition, ethylene-α-olefin copolymers whose lower limit of the content ratio of ethylene units is 60% by mass are particularly preferred.

[0085] The above-mentioned styrene-based elastomer refers to a copolymer having a structural unit derived from an aromatic vinyl compound. Generally, a block including a structural unit derived from an aromatic vinyl compound exhibits thermoplasticity and constitutes a hard segment.

[0086] The monomer constituting the hard segment may be an aromatic vinyl compound, and its type is not limited, and examples thereof include alkyl-substituted styrenes such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,5-dimethylstyrene, and 3,5-dimethylstyrene, vinylnaphthalene, vinylanthracene, etc. These aromatic vinyl compounds may be used alone or in combination of two or more.

[0087] On the other hand, as long as the block constituting the soft segment can show elastomer properties and function as a soft segment, any monomer can be used to form it, but preferably a conjugated diene is used. As the conjugated diene forming such a soft segment, butadiene, isoprene, chloroprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-methyl-1,3-octadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, 1,3-hexadiene, 1,3-cyclohexadiene, etc. can be cited. These conjugated dienes can be used only one kind, or two or more kinds can be used in combination.

[0088] Examples of styrene elastomers composed of styrene copolymers include styrene-isoprene-styrene block (SIS) copolymers, styrene-butadiene-styrene block (SBS) copolymers, styrene-ethylene-propylene-styrene block (SEPS) copolymers, etc. Furthermore, polymers in which a part or all of the structural units derived from styrene in these exemplified copolymers are replaced by structural units derived from styrene derivatives such as α-methylstyrene may be used. Such (non-hydrogenated) styrene elastomers may be used alone or in combination of two or more.

[0089] The hydrogenated styrene elastomer may be a product obtained by hydrogenating a styrene copolymer constituting the non-hydrogenated styrene elastomer, and examples thereof include styrene-ethylene-butylene-styrene block (SEBS) copolymers, hydrogenated styrene-butadiene-styrene block copolymers (HSBR), etc. Such hydrogenated styrene elastomers may be used alone or in combination of two or more.

[0090] The thermoplastic elastomer component (A) of the present invention may be an acid-modified thermoplastic elastomer or an amine-modified thermoplastic elastomer. Examples of the acid-modified thermoplastic elastomer include acid-modified styrene elastomers such as maleic acid-modified styrene elastomers and fumaric acid-modified styrene elastomers, and acid-modified olefin elastomers such as maleic acid-modified olefin elastomers and fumaric acid-modified olefin elastomers. In addition, the amine-modified thermoplastic elastomer is an amine-modified styrene elastomer. Among them, the acid-modified styrene elastomer is preferred.

[0091] The thermoplastic elastomer component (A) contained in the thermoplastic elastomer composition may be only one kind or two or more kinds.

[0092] As the raw material for the thermoplastic elastomer component (A), a commercially available product can be used.

[0093] Specific examples of the styrene copolymers (styrene thermoplastic elastomers) include Kraton G (G1642, G1652, G1730, etc.) manufactured by Kraton Polymers Japan, Kraton D (D1101, D1102, D1155, D1192, D1161, D1171, DKX405, DKX410, DKX415, etc.) manufactured by Kraton Polymers Japan, JSR-TR (JSR-TR1086, JSR-TR1600, etc.) manufactured by JSR, JSR-SIS (JSR-SIS), Dynaron (Dynaron), Taftec (Taftec H series, Taftec P series, etc.) manufactured by Asahi Kasei Corporation, and Tufprene (Tufprene A, Tufprene 125, Tufprene 126S, etc.), Asahi Kasei Corporation's trade name "Asaprene", Asahi Kasei Corporation's trade name "Solprene", Kuraray Co., Ltd.'s trade name "Septone", Kuraray Co., Ltd.'s trade name "Hibrane", Sumitomo Chemical Co., Ltd.'s trade name "Espolex SB", Mitsubishi Chemical Co., Ltd.'s trade names "Laboron" and "Techafloc", Denka STR manufactured by Denki Kagaku Co., Ltd.'s trade name "Quintake" manufactured by Nippon Zeon Co., Ltd., and Riken Technos Co., Ltd.'s trade name "Leostmark", etc.

[0094] Examples of the acid-modified styrene-based elastomer include "Taftec M1913" manufactured by Asahi Kasei Corporation, and examples of the acid-modified olefin-based elastomer include "Tafmer MP0610" manufactured by Mitsubishi Chemical Corporation.

[0095] Examples of the amine-modified thermoplastic styrene-based elastomer include "Tuftec MP10" (trade name) manufactured by Asahi Kasei Corporation.

[0096] These may be used alone or in combination of two or more. In addition, these product names also include "registered trademarks".

[0097] [Olefin resin component (B)]

[0098] The olefin resin component (B) of the present invention plays a connecting role when mixing and preparing the resin composition of the present invention. It also imparts strength and wear resistance to the resin composition of the present invention and the obtained anti-slip mat, and has the function of appropriately controlling the specific gravity. In addition, it has the function of improving the moldability during injection molding.

[0099] The above-mentioned olefin-based resin component (B) is not particularly limited as long as it is a resin having ethylene units or α-olefin units, and examples thereof include: resins including low-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, syndiotactic polypropylene, isotactic polypropylene, ethylene-α-olefin copolymers, and their modified resins.

[0100] In the present invention, when the thermoplastic elastomer component (A) is a styrene-based elastomer, an olefin-based elastomer or a hydrogenated styrene-based elastomer, the olefin-based resin component (B) is preferably a resin having an α-olefin unit, more preferably a polypropylene resin and an ethylene-α-olefin copolymer (wherein the upper limit of the content of the ethylene unit is 40% by mass), and particularly preferably a polypropylene resin, from the viewpoint of excellent miscibility and compatibility.

[0101] When the olefin resin component (B) is a modified resin, an olefin resin containing a polar group such as a glycidyl group, a carboxyl group, or an acid anhydride group can be used.

[0102] Examples of the glycidyl group-containing olefin resin include ethylene-glycidyl methacrylate copolymers and the like.

[0103] Examples of the acid anhydride group-containing olefin resin include maleic anhydride-modified polypropylene, maleic anhydride-modified polyethylene, and ethylene-maleic anhydride copolymers.

[0104] As the raw material for the olefin-based resin component (B), commercially available products can be used.

[0105] Specific examples of maleic anhydride-modified polypropylene include "Admer QF" manufactured by Mitsui Chemicals, "U-MAX" manufactured by Sanyo Chemical, and "Rikeide MG" manufactured by Riken Vitamin Co., Ltd.

[0106] Specific examples of maleic anhydride-modified polyethylene include trade names "Admer LF, NF" manufactured by Mitsui Chemicals, Inc., and the like.

[0107] Specific examples of the ethylene-maleic anhydride copolymer include "LOTADERMAH" manufactured by Arkema and "BONDAIN" manufactured by Sumitomo Chemical.

[0108] Specific examples of the ethylene-glycidyl methacrylate copolymer include "BOND FIBERST" manufactured by Sumitomo Chemical Co., Ltd. and "LOTADER GMA" manufactured by Arkema Corporation.

[0109] These olefin-based resins may be used alone or in combination of two or more.

[0110] As the above-mentioned olefin-based resin component (B), ethylene-α-olefin copolymers, polypropylene resins, and maleic anhydride-modified polypropylene are preferred from the viewpoint of low specific gravity of the resin, and polypropylene resins and maleic anhydride-modified polypropylene are more preferred from the viewpoint of miscibility and compatibility with the thermoplastic elastomer component (A).

[0111] As the olefin resin component (B), when specified by melt flow rate (hereinafter also referred to as "MFR"), a resin of 1 to 100 g / 10 minutes is preferred. When the melt flow rate is less than 1 g / 10 minutes, the fluidity of the resin composition of the present invention decreases and the moldability deteriorates. On the other hand, when the melt flow rate is greater than 100 g / 10 minutes, the strength and wear resistance of the obtained anti-skid mat decrease.

[0112] It is more preferably 3 to 70 g / 10 minutes, further preferably 5 to 50 g / 10 minutes, and particularly preferably 10 to 40 g / 10 minutes.

[0113] The melt flow rate is determined by the molecular weight of the olefin resin component (B) and serves as a criterion for the moldability and strength of the resin composition. The melt flow rate is measured at a temperature of 230° C. and a load of 21.18 N in accordance with JIS K7201-1.

[0114] The raw material resin used for the olefin resin component (B) may contain fillers such as talc, calcium carbonate, and glass fiber, antioxidants, weather resistance imparting agents, and the like.

[0115] [Softener ingredient (C)]

[0116] The softener component (C) is not particularly limited, but preferably has compatibility with the thermoplastic elastomer component (A). Thus, it is possible to suppress undesirable conditions such as the softener component (C) seeping out from the obtained molded product. From this viewpoint, preferred softener components (C) include rubber softeners such as paraffin oil, naphthenic oil, and aromatic oil.

[0117] The softener component (C) contained in the thermoplastic elastomer composition may be only one kind or two or more kinds.

[0118] Among thermoplastic elastomers, paraffin oil is particularly preferred from the viewpoint of good compatibility with styrene elastomers and less prone to bleed out.

[0119] The paraffin oil is preferably a paraffin oil having a high dynamic viscosity at 40° C. Specifically, from the viewpoint of preventing volatilization during heating and melting and improving the anti-bleeding property, a viscosity of 30 mm 2 / s or more, more preferably 60mm 2 / s or more, more preferably 80mm2 / s or more. In addition, if it is also assumed that the composite with a polar resin is used, 150 mm is particularly preferred from the viewpoint of improving the weldability. 2 On the other hand, from the viewpoint of easy handling, the dynamic viscosity is preferably 500 mm 2 / s or less, more preferably 450mm 2 / s or less, more preferably 400mm 2 / s or less. From the viewpoint of improving wear resistance, 200 mm is particularly preferred. 2 / s or less.

[0120] In addition, the dynamic viscosity is measured according to JIS K2283.

[0121] In order to satisfy the physical properties such as flexibility, strength and wear resistance, the thermoplastic elastomer composition of the present invention contains a thermoplastic elastomer component (A), an olefin resin component (B) and a softener component (C), wherein the content of the component (B) is preferably 10 to 90 parts by mass, and the content of the component (C) is preferably 100 to 300 parts by mass, based on 100 parts by mass of the component (A).

[0122] The content of component (B) is more preferably 15 to 70 parts by mass, and even more preferably 15 to 50 parts by mass. The content of component (C) is more preferably 110 to 250 parts by mass, and even more preferably 110 to 200 parts by mass.

[0123] From the viewpoint of moldability and the wear resistance and softness of the obtained anti-slip mat, when the resin composition for anti-slip mat is set to 100 mass %, the content of the thermoplastic elastomer composition constituting the resin composition for anti-slip mat of the present invention is 80 mass % or less, preferably 26 to 80 mass %, more preferably 30 to 75 mass %, and further preferably 35 to 70 mass %. It should be noted that when the content of the thermoplastic elastomer composition is less than 26 mass %, the content of the thermoplastic elastomer component (A) may be too small, and the moldability may be insufficient.

[0124] [Anti-mold agent]

[0125] When the anti-slip mat resin composition of the present invention contains a mildew preventer, the anti-slip mat after contact with water can prevent the growth of molds, which are fungi. Therefore, when the anti-slip mat containing a mildew preventer is used at the edge or bottom of a pool, in a bathroom or a bathtub, etc., the growth of molds can be prevented, so it is hygienic.

[0126] The above-mentioned antifungal agent is not particularly limited, but is preferably an antifungal agent having good compatibility and dispersibility with the component (A) or the component (C) constituting the thermoplastic elastomer composition.

[0127] The above-mentioned antifungal agent may be any of a synthetic antifungal agent and a natural antifungal agent.

[0128] Examples of synthetic antifungal agents include thiabendazole; pyrithione zinc and the like; metal salts; imidazole compounds such as methyl 2-benzimidazolecarbamate, methyl 1-(butylcarbamoyl)benzimidazole-2-carbamate, and enilconazole; phthalimide compounds such as N-(trichloromethylthio)phthalimide; amine compounds such as aluminum N-nitrosocyclohexylhydroxylamine; nitrile compounds such as 2,4,5,6-tetrachloroisophthalonitrile; benzothiazole compounds such as 2-(thiocyanatomethylthio)benzothiazole; thiocyanate compounds such as methylene dithiocyanate; o-phenylphenol (OPP) compounds such as sodium salt of o-phenylphenol; fluorine Phenylpyrrole compounds such as Fludioxonil; Anilinopyrimidine compounds such as Pyrimethanil; Strobilurin compounds such as Azoxystrobine; Halogenated phenol compounds such as Parachlorometaxylenol, etc.

[0129] Moreover, as a natural type antifungal agent, a hinokitiol, thymol, d-limonene etc. are mentioned, for example.

[0130] In addition, the said antifungal agent can be used individually or in combination of 2 or more types.

[0131] Among the above-mentioned antifungal agents, thiabendazole and pyridine are preferred from the viewpoint of compatibility with the thermoplastic elastomer composition and dispersibility in the resin composition for the anti-slip mat of the present invention. Metal salts.

[0132] As the above-mentioned antifungal agent, a commercially available synthetic antifungal agent can be used.

[0133] Examples of commercially available synthetic antifungal agents include: "Non-Toro", "Seto-Toro", "Toro" manufactured by Sumika Environmental Science Co., Ltd., and "Toro" manufactured by MIC Co., Ltd.ィックビーム", trade name "バクテキラー" manufactured by Fuji Chemical Co., Ltd., manufactured by Sanai Oil Co., Ltd. The trade name is "Surcontech", the trade name of Lanxess Co., Ltd. is "Hydrotron", etc.

[0134] When the anti-slip mat resin composition of the present invention contains a mildew preventer, the content of the mildew preventer is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 8 parts by mass, further preferably 0.03 to 7 parts by mass, and particularly preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the thermoplastic elastomer component (A) constituting the thermoplastic elastomer composition. When the content of the mildew preventer is greater than 10 parts by mass, the anti-slip mat resin composition of the present invention may become sticky, or blooming (whitening) may occur on the molded article, resulting in a deteriorated appearance, or deterioration in abrasion resistance, etc.

[0135] The resin composition for an anti-slip mat of the present invention may contain other ingredients as needed within a range that does not impair the physical properties.

[0136] Examples of other additives include fillers, weather resistance imparting agents, antioxidants, lubricants, pigments / dyes, polar group-containing resins, and processing aids, but are not limited thereto.

[0137] The following is a specific description.

[0138] [Bulking Agent]

[0139] The resin composition for an anti-slip mat of the present invention may contain other fillers in order to adjust the strength and specific gravity.

[0140] Other fillers include: metal powders such as tungsten alloy, stainless steel alloy, copper, iron, and aluminum; inorganic fillers such as heavy calcium carbonate, light calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, antimony trioxide, titanium oxide, talc, mica, and clay; and reinforcing fibers such as rock wool, slag wool, glass wool, and glass fiber.

[0141] [Weather resistance imparting agent]

[0142] When the resin composition for an anti-slip mat of the present invention contains a weather resistance imparting agent, when the anti-slip mat is hung outdoors to dry after being used outdoors or after being used indoors, the anti-slip mat is exposed to sunlight, thereby suppressing photodeterioration of the anti-slip mat.

[0143] Examples of the weather resistance imparting agent include ultraviolet absorbers such as benzotriazole-based, benzophenone-based, benzoate-based, and cyanoacrylate-based ultraviolet absorbers and light stabilizers such as HALS (hindered amine-based).

[0144] [Antioxidant]

[0145] In the process of producing the resin composition for the anti-slip mat of the present invention by a kneader or in the process of producing the anti-slip mat by injection molding, an antioxidant may be used to suppress the deterioration of physical properties and color tone when the resin composition for the anti-slip mat is heated.

[0146] Examples of the antioxidant include hindered phenol compounds, amine compounds, phosphite compounds, phosphate compounds, sulfur compounds, etc. These antioxidants may be used alone or in combination of two or more.

[0147] Examples of hindered phenol antioxidants include 2,4-dimethyl-6-tert-butylphenol, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, hydroxymethyl-2,6-di-tert-butylphenol, 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 2,5-di-tert-butyl-4-ethylphenol, 4,4'-bis(2,6-di-tert-butylphenol), 2,2'-methylene-bis-4-methyl-6-tert-butylphenol, 2,2'-methylene-bis(4-ethyl-6-tert-butylphenol), 4,4'-methylene-bis(6-tert-butyl-o-cresol), ...2,4'-bis(6-tert-butyl-o-cresol), 2,4'-bis(2,6-di-tert-butylphenol), 2,4'-bis(4-ethyl-6-tert-butylphenol), 2,4'-bis(2,6-di-tert-butylphenol), 2,4'-bis(2,6-di-tert-butylphenol), 2,4'-bis(4-ethyl-6-tert-butylphenol), 2,4'-bis(2,6-di-tert-butylphenol), 2,4'-bis(2,6-di-tert Methylene-bis(2,6-di-tert-butylphenol), 2,2'-methylene-bis(4-methyl-6-cyclohexylphenol), 4,4'-butylene-bis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), bis(3-methyl-4-hydroxy-5-tert-butylbenzyl) sulfide, 4,4'-thiobis(6-tert-butyl-o-cresol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), 2,6-bis(2'-hydroxy-3'-tert-butyl-5'-methylbenzyl)-4-methylphenol, 3,5-di-tert-butyl-4 -Diethyl hydroxybenzenesulfonate, 2,2'-dihydroxy-3,3'-di(α-methylcyclohexyl)-5,5'-dimethyl-diphenylmethane, α-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate, 6-(hydroxy-3,5-di-tert-butylanilino)-2,4-bis(octylthio)-1,3,5-triazine, hexamethylene glycol-bis[β-(3,5-di-tert-butyl-4-hydroxyphenol) propionate], N,N'-hexamethylene-bis(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid amide), 2,2-thio[diethyl-bis- 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 3,5-di-tert-butyl-4-hydroxyphenylphosphonic acid distearyl, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]methane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 1,1,3-tris(2-methyl-4-hydroxy-5-di-tert-butylphenyl)butane, tris(3,5-di-tert-butyl-4-hydroxyphenyl) isocyanurate, tris[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyloxyethyl] isocyanurate, etc.

[0148] Among them, compounds having a molecular weight of 500 or more such as tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane are preferred.

[0149] Examples of the amine antioxidant include phenylnaphthylamine, 4,4'-dimethoxydiphenylamine, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, and 4-isopropoxydiphenylamine.

[0150] Examples of the phosphite antioxidant include tetrakis[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-5-methylphenyl]-1,6-hexamethylene-bis(N-hydroxyethyl-N-methylsemicarbazide)-diphosphite, tetrakis[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-5-methylphenyl]-1,10-decamethylene-dicarboxylic acid-dihydroxyethylcarbonylhydrazide-diphosphite, tetrakis[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-5-methylphenyl]-1,6-hexamethylene-bis(N-hydroxyethyl-N-methylsemicarbazide)-diphosphite -methyl-4'-hydroxy-5'-tert-butylphenyl)-5-methylphenyl]-1,10-decamethylene-dicarboxylic acid-disalicylic hydrazide-diphosphite, tetrakis[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-5-methylphenyl]-bis(hydroxyethylcarbonyl)hydrazide-diphosphite, tetrakis[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butylphenyl)-5-methylphenyl]-N,N'-bis(hydroxyethyl)oxalamide-diphosphite, etc.

[0151] In the present invention, a phosphite-based compound in which at least one PO bond or P═O bond is bonded to an aromatic group is preferred.

[0152] Examples of the phosphite-based compounds include tris(2,4-di-tert-butylphenyl)phosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenyl diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol-diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol-diphosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite, 4,4'-butylene-bis(3-methyl-6-tert-butylphenyl)octylphosphite, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol-diphosphite. butylphenyl-ditidecyl) phosphite, 1,1,3-tris(2-methyl-4-ditridecylphosphite-5-tert-butylphenyl)butane, tris(mixed mono- and di-nonylphenyl)phosphite, tris(nonylphenyl)phosphite, 4,4'-isopropylidenebis(phenyl-dialkylphosphite), 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and the like.

[0153] In addition to the above antioxidants, other antioxidants such as phosphate compounds and sulfur compounds may be used.

[0154] [Lubricant]

[0155] The resin composition for an anti-slip mat of the present invention may contain a lubricant in order to improve molding processability when producing the resin composition for an anti-slip mat of the present invention, or in order to improve releasability from a mold when producing the anti-slip mat of the present invention.

[0156] Examples of the lubricant include fatty acids, fatty amides, esters, alcohols, metal soaps, silicone oils, silicone resins, and fluorine resins.

[0157] Examples of the fatty acid-based lubricant include myristic acid, palmitic acid, stearic acid, arachidic acid, and behenic acid.

[0158] Examples of the fatty amide lubricant include stearic acid amide, palmitamide, oleic acid amide, methylene bisstearic acid amide, and ethylene bisstearic acid amide.

[0159] Examples of the ester lubricant include lower alcohol esters of fatty acids, polyol esters of fatty acids, and polyglycol esters of fatty acids.

[0160] Examples of the alcohol-based lubricant include cetyl alcohol, stearyl alcohol, and polyethylene glycol.

[0161] Examples of the metal soap-based lubricant include zinc stearate, calcium stearate, aluminum stearate, 12-hydroxystearate zinc, and 12-hydroxystearate calcium.

[0162] In addition, silicone oil, silicone resin, fluorine resin, etc. can also be used.

[0163] [Colorants (pigments and dyes)]

[0164] When the anti-slip mat of the present invention is desired to be colored in an arbitrary color, a colorant may be used.

[0165] As a coloring method, a method of adding a colorant such as a pigment or dye, a masterbatch of a colorant, etc. when manufacturing the resin composition for the anti-slip mat of the present invention can be cited. In addition, a method of not adding a colorant to the resin composition of the present invention and manufacturing it in a natural color, and a method of adding a colorant such as a pigment or dye, or a masterbatch of a colorant, etc. when manufacturing the anti-slip mat of the present invention can be cited.

[0166] As the pigment or dye, organic and inorganic pigments or dyes are known, and any common pigment or dye can be used as long as it can withstand the heat during molding.

[0167] [Polar group-containing resin]

[0168] When producing the resin composition for an anti-slip mat of the present invention or when producing an anti-slip mat, a polar group-containing resin may be contained in order to increase the tension of the melt and improve the ductility.

[0169] The polar group-containing resin is a resin other than the acid-modified thermoplastic elastomer and the polar group-containing olefin resin, and specific examples thereof include polyester resins, polyamide resins, and polycarbonate resins.

[0170] In addition, the resin composition for anti-slip mats of the present invention may contain processing aids such as acrylic modified polytetrafluoroethylene and high molecular weight special acrylic resins, antistatic agents, fire retardants, oil retardants, chelating agents, pigment dispersants, etc.

[0171] When the anti-slip mat resin composition of the present invention contains other additives (excluding mildewproofing agents), the content ratio of the other additives relative to the anti-slip mat resin composition is preferably 10% by mass or less. When it is greater than 10% by mass, the surface of the obtained molded product may become sticky, or the strength, wear resistance and anti-slip properties of the molded product may be reduced.

[0172] From the viewpoint of moldability, the resin composition for an anti-slip mat of the present invention preferably has a melt flow rate of more than 0.1 g / min at a temperature of 230° C. and a load of 98 N as measured in accordance with JIS K7210-1.

[0173] The melt flow rate is more preferably 0.2 g / 10 min or more, further preferably 0.5 g / 10 min or more, and particularly preferably 1 g / 10 min or more. When the melt flow rate is greater than 0.1 g / 10 min, moldability during injection molding becomes good.

[0174] The resin composition for an anti-slip mat of the present invention can be produced by mixing and kneading synthetic barium sulfate with the thermoplastic elastomer component (A), the olefin resin component (B) and the softener component (C) constituting the thermoplastic elastomer composition and various additives (antifungal agent, etc.) as needed.

[0175] The raw material components are mixed using, for example, a mixing device such as a Henschel mixer, a high-speed mixer, or a drum mixer. The resulting mixture is then melt-mixed and extruded into strips by an extruder, and is cut into particles by a cutter while cooling in cold water. The particles obtained are usually formed into a specified molded product by injection molding or extrusion molding. In addition, the mixed composition can also be made into particles by an extruder or the like to form a molding processing raw material.

[0176] In order to improve the productivity of the resin composition for anti-slip mats of the present invention, the mixing device used is preferably a continuous type such as an extruder. The extruder can use a multi-screw extruder such as a single-screw extruder, a twin-screw extruder, and a four-screw extruder. From the viewpoint of mixing power and productivity, a twin-screw extruder is more preferred.

[0177] The resin composition for an anti-slip mat produced as described above has a type A durometer hardness of 20 to 80.

[0178] The anti-slip mat of the present invention is a molded product comprising the resin composition for anti-slip mats of the present invention. The resin composition for anti-slip mats of the present invention and the anti-slip mat comprising the resin composition for anti-slip mats of the present invention are characterized in that the A-type durometer hardness measured according to JIS K6253 is 20 to 80. Since the A-type durometer hardness is within the above range, the molded product anti-slip mat is not too soft, and there is no bottoming feeling when using it, and it does not feel uncomfortable. In addition, it is also easy to fold or curl the anti-slip mat.

[0179] The type A durometer hardness is preferably 30-70, more preferably 40-70, particularly preferably 50-70.

[0180] The anti-slip mat comprising the resin composition for anti-slip mats of the present invention is sometimes immersed in a bathtub or a pool for use, so the larger the specific gravity, the better. However, if it is too heavy, it is difficult for the elderly to carry it, and there is a concern of back and leg pain during operation. There is also a concern of falling and getting injured during operation.

[0181] Therefore, the specific gravity of the resin composition for anti-slip mats and the anti-slip mats of the present invention is preferably greater than 1.0 and less than 2.2. When the specific gravity is 1.0 or less, it does not sink in water. When the specific gravity is 2.2 or more, it is difficult for the elderly and the like to handle.

[0182] A more preferred range is greater than 1.1 and less than 2.1, a more preferred range is greater than 1.2 and less than 2.0, and a particularly preferred range is greater than 1.4 and less than 1.9.

[0183] The specific gravity of the resin composition for anti-slip mat and the anti-slip mat of the present invention can be selected from the above ranges according to the purpose of use so that the self-sinking time of the anti-slip mat is short and the handling is easy, and can be controlled by the amount of synthetic barium sulfate or olefin resin used.

[0184] The anti-slip mat comprising the resin composition for an anti-slip mat of the present invention needs to have wear resistance that can withstand repeated actions such as friction and pressing when a user sits or walks.

[0185] As the wear resistance required of the anti-slip mat composition of the present invention, the anti-slip mat resin composition preferably has an abrasion loss mass of less than 1000 mg in the Taber abrasion test according to JIS K7204, more preferably less than 800 mg, further preferably less than 500 mg, and particularly preferably less than 200 mg.

[0186] Such low wear loss mass can be achieved by using synthetic barium sulfate.

[0187] The self-sinking speed of the anti-slip mat comprising the resin composition for anti-slip mats of the present invention is preferably less than 8 seconds. From the perspective of ease of use for users, it is more preferably less than 6 seconds. It is further preferably less than 5 seconds, and particularly preferably less than 4 seconds. If the self-sinking speed is greater than 8 seconds, the user may step on the mat before it fully sinks, and in this case, there is a fear of slipping.

[0188] The shape and size of the anti-slip mat of the present invention can be appropriately set according to the place and purpose of use. For example, in the case of a bathroom or a bathtub, it is usually in a plate shape from the viewpoint of quality and easy carrying, and can be 10 to 100 cm in width, 20 to 200 cm in length, and 0.05 to 2 cm in thickness. The projection shape of the width and length can be square, rectangular, circular, oval, etc., or can be any shape.

[0189] As the size when used in a bathroom, bathtub, etc., the width is preferably 15 to 80 cm, more preferably 20 to 60 cm, and even more preferably 25 to 50 cm. The length is preferably 30 to 160 cm, more preferably 40 to 120 cm, and even more preferably 50 to 100 cm. In addition, the thickness is preferably 0.07 to 1.5 cm, more preferably 0.1 to 1 cm, and even more preferably 0.15 to 0.8 cm.

[0190] The mass of the anti-slip mat of the present invention is preferably less than 5 kg, more preferably less than 4 kg, further preferably less than 3 kg, and most preferably less than 2 kg, from the viewpoint of user handling.

[0191] The color tone of the anti-slip mat of the present invention can be arbitrarily determined, but generally, a striking color such as red, green, or blue is preferred so that the mat can be easily recognized at a glance.

[0192] In addition, in order to further improve the anti-slip effect, the surface and / or back of the anti-slip mat of the present invention can be provided with convex parts or concave parts, etc., and these convex parts or concave parts have a grid-type, concentric circle-type, or dot-type (dot-shaped) pattern formed by embossing or the like.

[0193] As described above, the specific gravity of the anti-slip mat of the present invention is preferably greater than 1.0 and less than 2.2. In addition, the abrasion loss mass based on the Taber abrasion test is preferably less than 1000 mg.

[0194] The anti-slip mat of the present invention is useful for preventing falls on wet floors or in water, and can be used in bathrooms or bathtubs, poolsides or bottoms, toilet floors, entrances that are easily wetted by rainwater, bus hatches, etc. Among them, it is preferably used in bathrooms or bathtubs where there are many falls by the elderly, and is particularly preferably used in bathtubs.

[0195] The manufacturing method of the anti-slip mat of the present invention is not particularly limited and can be appropriately selected according to the shape and size. In the present invention, compression molding, injection molding, and extrusion molding can be used. Among them, injection molding is preferred from the viewpoint of productivity and economy.

[0196] In the case of injection molding, the specifications of a mold used in an injection molding machine can be set arbitrarily.

[0197] As the cavity structure in the mold, it is preferable to set the flow ratio (L (flow distance) / t (wall thickness)) to an optimal range. Here, L represents the farthest position to be filled in the cavity from the gate where the molten resin flows into the mold.

[0198] In the present invention, L / t is preferably less than 155 when t=0.5 to 5 mm. When L / t is 155 or more, the resin composition for anti-slip mats of the present invention cannot be completely filled into the mold, and a molded product of a desired shape / size may not be obtained. A more preferred L / t is less than 145, and more preferably less than 140, from the viewpoint of the appearance (flow marks, etc.) of the molded product.

[0199] Example

[0200] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "mass %" respectively.

[0201] [Production Conditions of Thermoplastic Elastomer Composition]

[0202] A thermoplastic elastomer (component (A)), an olefin resin (component (B)), barium sulfate, a mildewproofing agent as required, and other components are dry-blended, and a softener (component (C)) is impregnated therein to prepare a mixture. Next, the mixture is melt-kneaded by an extruder under the following conditions to prepare a base material (pellets) of the thermoplastic elastomer composition.

[0203] Twin-screw extruder···KZW32TW-60MG (trade name, manufactured by Technobell)

[0204] Barrel temperature···180~220℃

[0205] Screw speed···300rpm

[0206] [Injection molding conditions of test sheet 1]

[0207] Injection molding was performed under the following conditions to obtain a test sheet 1 having a thickness of 2 mm×a width of 125 mm×a length of 125 mm.

[0208] Injection molding machine: Mitsubishi Heavy Industries, Ltd. "100MSIII-10E" (model name)

[0209] Injection molding temperature: 230℃

[0210] Injection pressure: 39MPa

[0211] Injection time: 10 sec

[0212] Mold temperature: 40℃

[0213] Mold internal shape: Cavity shape; cuboid with a thickness of 2mm, a width of 125mm, and a length of 125mm

[0214] Gate location: upper end of cavity (L / t=62.5)

[0215] Gate shape: film gate

[0216] The compounding ratios, measurements, and evaluation results are shown in Tables 1 to 3.

[0217] [Injection molding conditions of test sheet 2]

[0218] The injection molding was performed under the following conditions to obtain a test sheet 2 having a thickness of 3 mm×a width of 380 mm×a length of 200 mm.

[0219] Injection molding machine: Mitsubishi Heavy Industries, Ltd. "100MSI II-10E" (model name)

[0220] Injection molding temperature: 230℃

[0221] Injection pressure: 40MPa

[0222] Injection time: 10 sec

[0223] Mold temperature: 40℃

[0224] Mold internal shape: Cavity shape; cuboid with thickness 3mm, width 380mm and length 200mm

[0225] Gate location: center on the diagonal line of the cavity plane (L / t=71.6)

[0226] Gate shape: pin point gate

[0227] The compounding ratios, measurements, and evaluation results are shown in Tables 1 to 3.

[0228] [Physical property measurement method]

[0229] The physical property measurement method of the evaluation sample is as follows: The mass of the sample was measured using an electronic balance "GF-203A" (model name) manufactured by A&D Corporation.

[0230] (1) Type A durometer hardness

[0231] The test piece formed by stacking three test sheets 1 having a thickness of 2 mm (total 6 mm) which were placed in a room at a temperature of 23° C. and a humidity of 50% for one day and conditioned was measured for the A-type durometer hardness 15 seconds after the start of the measurement in accordance with JIS K6253. The measuring instrument was a constant pressure load meter "CL-150L" (model name) equipped with a digital rubber hardness meter "DD4-2" (model name) manufactured by ASKER. The load was set to 1000 g.

[0232] (2) Specific gravity

[0233] A test piece of 3 cm x 3 cm was cut out from the test sheet 1 conditioned in a room at 23°C and 50% humidity for one day, and measured in accordance with JIS K7112. The measuring instrument was an electronic densimeter "SD-200L" (model name) manufactured by ALFA MIRAGE.

[0234] (3) Tensile test (tensile strength and elongation at break)

[0235] From the test sheet 1 which was placed in a room at a temperature of 23°C and a humidity of 50% for one day and conditioned, a demolding machine was used to make a No. 3 test piece described in JIS K7113, and a marking line of ±10mm (the total width of the marking line is 20mm) was drawn from the center of the parallel part of the dumbbell. Next, a tensile testing machine "Autograph AG-50ND" (model name) manufactured by Shimadzu Corporation was used to stretch the test piece at a speed of 500mm / min at a temperature of 23°C. The stress (MPa) at the time of the test piece breaking was recorded as the tensile strength. In addition, the distance between the marking lines of the parallel parts of the dumbbell at the time of breaking was measured at the same time, and the elongation at break was calculated by subtracting it from the initial value of 20mm. The greater the tensile strength, the better the mechanical strength.

[0236] (4) Taber abrasion test

[0237] A sample punched out into a 10.8 cm diameter disc from a test sheet 1 that had been placed in a room at a temperature of 23°C and a humidity of 50% for one day and conditioned was used. A wear test was performed at 23°C in accordance with JIS K7204, wherein the grinding wheel was H-22, the rotation speed was 72 rpm, the number of rotations was 1000 times, the load was 1000 g, and the wear loss mass (mg) was measured from the difference between the mass of the sample before and after the test. The measuring instrument was a rotary wear tester "TS-2" (model name) manufactured by Toyo Seiki Seisaku-sho Co., Ltd.

[0238] (5) Melt flow rate

[0239] Using a substrate (pellet), the measurement was performed based on JIS K7210-1 at a temperature of 230°C and a load of 21.18N. At this time, data less than 0.1g / 10min was set to "NF", and the load was changed to 49.18N for re-measurement. At this time, data less than 0.1g / 10min was also set to "NF", and the load was changed to 98.18N for re-measurement. At this time, data less than 0.1g / 10min was also set to "NF" (here, "NF" means "non-flowing"). The measuring instrument is "Melt Indicator" (trade name) manufactured by Toyo Seiki Seisaku-sho, Ltd.

[0240] (6) Sliding test

[0241] The sliding resistance coefficient (CSR·B value) was determined in accordance with JIS A1509-12 "Ceramic Tile Test Methods - Part 12 Sliding Resistance Test Method" using a test piece of 135 mm in length and 90 mm in width cut out from the test sheet 2. A weight of 4.31 N was used as the load.

[0242] (7) Self-sinking test

[0243] Using a test sheet 2 of 380 mm in width × 200 mm in length × 3 mm in thickness, in a transparent acrylic resin container (500 mm in width × 500 mm in length × 500 mm in height) filled with 30 cm of water, one end of the sample (200 mm in length side) is mounted on the bottom of the container, and the other end of the sample is maintained at the height of the water surface, so as to set the sample in a cantilevered inclined state in the water.

[0244] Then, the end of the sample on the water surface side is opened, and the time until this end sinks to the bottom of the container is calculated.

[0245] (8) Chlorine water test

[0246] Add 1 sheet of "Furomizu Wonder" (trade name) manufactured by Kao Corporation to 50L of warm water (40°C). Then, immerse the test sheet 1 in the warm water and maintain the temperature (40°C). After 4 hours, take out the test sheet 1 and wipe off the water droplets. Then, place it in a room with a temperature of 23°C and a humidity of 50% for 24 hours to adjust the state. After the state is adjusted, touch it with your fingers and conduct a sensory test for stickiness.

[0247] (9) Anti-mildew test

[0248] A 3 cm × 3 cm test piece was cut out from the test sheet 1, and according to JIS Z2911 (antifungal test method, Appendix A test for plastic products), a suspension of the five-bacteria composite was dripped onto each test piece on an agar medium, and the test pieces were cultured at a specified temperature and humidity for 4 weeks, and the development state of the hyphae on the test pieces was evaluated.

[0249] The evaluation was performed using the following six levels of 0 to 5.

[0250] “0”: No mold development was observed under the naked eye or microscope.

[0251] "1": No fungal growth is visible to the naked eye, but can be clearly confirmed under a microscope.

[0252] "2": No mold growth is visible to the naked eye, and the growth area is less than 25% of the total sample area.

[0253] "3": No mold growth is visible to the naked eye, and the growth area is more than 25% and less than 50% of the total sample area.

[0254] “4”: The mycelium is well developed, and the developed area accounts for more than 50% of the total area of ​​the sample.

[0255] “5”: The mycelium develops vigorously and the mold covers the entire sample.

[0256] [Materials for testing]

[0257] The materials used in the tests in Tables 1 to 3 (materials used for producing the resin composition for an anti-slip mat) are as follows.

[0258] (1) Thermoplastic elastomer A1: SEBS "GLOBALPRENE 7551U" (trade name) manufactured by LCY Chemical Co., Ltd., hydrogenated styrene-butadiene-styrene block copolymer, styrene content 33% by mass, weight average molecular weight 200,000

[0259] (2) Thermoplastic elastomer A2: Kraton D1102 (trade name) manufactured by Kraton Polymer Co., Ltd., hydrogenated styrene-butadiene-styrene block copolymer, styrene content 30% by mass, weight average molecular weight 110,000

[0260] (3) Thermoplastic elastomer A3: Ethylene-1-octene copolymer elastomer manufactured by The Dow Chemical Company, 1-octene content 22% by mass

[0261] (4) Olefin resin: "POLIMAXX 1100RC" (trade name) manufactured by IRPC Public Company, polypropylene (homopolymer), melt flow rate: 20 g / 10 min (230° C., 21.18 N load)

[0262] (5) Softener: paraffin oil "LW500" (trade name) manufactured by Japan Sun Oil Co., Ltd., dynamic viscosity: 99.3 mm 2 / s(40℃)

[0263] (6) Antioxidant (phenolic): "Tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane" (trade name) manufactured by Songwon International AG

[0264] (7) Antioxidant (phosphite type): tris(2,4-di-tert-butylphenyl)phosphite "SONGNOX 1680" (trade name) manufactured by Songwon International AG

[0265] (8) Lubricant (amide type): Oleamide "Nyutron" (trade name) manufactured by Nippon Seika Co., Ltd.

[0266] (9) Synthetic barium sulfate 1: "Bariace B-34" (trade name) manufactured by Sakai Chemical Industry Co., Ltd., surface-treated grade, particle size: D10 = 0.1 μm, D50 = 0.2 μm, D90 = 0.4 μm

[0267] (10) Synthetic barium sulfate 2: "Sedimentary barium sulfate 300" (trade name) manufactured by Sakai Chemical Industry Co., Ltd., particle size: D10 = 0.4 μm, D50 = 0.7 μm, D90 = 1.6 μm

[0268] (11) Synthetic barium sulfate 3: "Barium sulfate B-1B" (trade name) manufactured by Sakai Chemical Industry Co., Ltd., particle size: D10 = 0.5 μm, D50 = 0.8 μm, D90 = 1.6 μm

[0269] (12) Synthetic barium sulfate 4: "BMH-100" (trade name) manufactured by Sakai Chemical Industry Co., Ltd., particle size: D10 = 1.5 μm, D50 = 11.6 μm, D90 = 28 μm

[0270] (13) Natural barium sulfate 1: "Barium sulfate BA" (trade name) manufactured by Sakai Chemical Industry Co., Ltd., particle size: D10 = 1.8 μm, D50 = 11.2 μm, D90 = 30.3 μm

[0271] (14) Natural barium sulfate 2: "Barium sulfate W-1" (trade name) manufactured by Takehara Chemical Industry Co., Ltd., particle size: D10 = 0.3 μm, D50 = 1.5 μm, D90 = 4.1 μm

[0272] (15) Antifungal agent: Thiopentazole "Sintole M-100" (trade name) manufactured by Sumika Environmental Science Co., Ltd.

[0273] (16) Antifungal agent: Pyrithione manufactured by Sumika Environmental Science Co., Ltd. Metal salt "Neither AF-80" (trade name)

[0274] (17) Antifungal agent: diiodomethyl-p-toluenesulfonic acid "Pachik Bim MOLD PBM-OK" (trade name) manufactured by MIC

[0275] 1. Production and evaluation of resin composition for anti-slip mat

[0276] In Table 1 and Table 2, as Examples 1 to 14 and Comparative Examples 1 to 6, a comparison between synthetic barium sulfate and natural barium sulfate, a comparison between the amounts of synthetic barium sulfate used, and a comparison between the types of thermoplastic elastomers, and the amounts of olefin resins and softeners used are described.

[0277] The raw materials listed in Tables 1 and 2 were kneaded by the extruder to produce the resin compositions for anti-slip mats of Examples 1 to 14 and Comparative Examples 1 to 6. Then, the A-type durometer hardness, specific gravity and MFR were measured, and a tensile test, Taber abrasion test, sliding test, self-sinking test and chlorine water resistance test were performed, and the results are recorded in Tables 1 and 2.

[0278]

[0279]

[0280] Table 3 shows the presence or absence of use of a fungicide and the comparison of the amount used as Examples 15 to 20.

[0281] The anti-fungal agent listed in Table 3 was added to the anti-slip mat resin composition of Example 1, and the obtained composition was kneaded by the above extruder to produce the anti-slip mat resin compositions of Examples 15 to 20. The amount of the anti-fungal agent listed in Table 3 is the amount of the thermoplastic elastomer (A1) of Example 1 per 100 parts by mass.

[0282] Then, a mildew proof test was performed under the same conditions as in Example 1, and the results are also shown in Table 3.

[0283] [Table 3]

[0284]

[0285] Based on Tables 1 to 3, the evaluation results are summarized as follows.

[0286] (1) In Examples 1, 3, 4, 5 and 7 using synthetic barium sulfate having a particle size D50 of less than 10 μm and using a styrene elastomer or a hydrogenated styrene elastomer as the thermoplastic elastomer, the abrasion loss mass was less than 200 mg, and the wear resistance was particularly good.

[0287] (2) From the comparison between Example 2 (using synthetic barium sulfate with a particle size D50 of 11.6 μm) and Comparative Example 1 (using natural barium sulfate with a particle size D50 of 11.2 μm), it can be seen that if a resin composition containing synthetic barium sulfate is used, a molded body with excellent wear resistance can be obtained.

[0288] (3) From the comparison between Examples 3 to 5 and Comparative Example 3, it can be seen that when the particle size of the synthetic barium sulfate is changed to different types and the amount is increased compared to Example 1 (Examples 3 to 5, in the pad resin composition, the amount is increased from 54 mass % to 66 mass %), the softness, high specific gravity and wear resistance (about 110 mg) are also good.

[0289] On the other hand, Comparative Example 3, in which natural barium sulfate was used in an increased amount compared with Comparative Example 1, had poor abrasion resistance (2329 mg) similarly to Comparative Example 1.

[0290] (4) From the comparison between Example 6 (using synthetic barium sulfate with a particle size D50 of 11.6 μm) and Comparative Example 4 (using natural barium sulfate with a particle size D50 of 1.5 μm), it can be seen that using a resin composition containing synthetic barium sulfate with a large particle size can also obtain a molded body with excellent wear resistance.

[0291] (5) In Examples 7 and 8, olefin elastomers or non-hydrogenated styrene elastomers were used as thermoplastic elastomers instead of hydrogenated styrene elastomers, and flexibility and high specific gravity were good. However, in Example 8, stickiness was generated in the chlorine water resistance test.

[0292] (6) Comparison between Example 9 and Comparative Examples 5 and 6 shows that Example 9, in which the amount of synthetic barium sulfate used in Example 1 was reduced (from 54% by mass to 30% by mass in the pad resin composition), also exhibited excellent flexibility and wear resistance. The specific gravity was reduced and the self-sinking time was prolonged, but it was within the practical range.

[0293] On the other hand, in Comparative Example 5, the synthetic barium sulfate content was excessively increased (75 mass%), but the A-type durometer hardness was excessively increased (hardness 83), and the wear resistance was greatly reduced (1497 mg). Furthermore, the melt flow rate was reduced, that is, the fluidity was reduced, and the moldability was deteriorated.

[0294] Comparative Example 6 is an example in which the content ratio of synthetic barium sulfate is reduced to outside the range of the present invention (15 mass %), but the specific gravity is less than 1 and it does not sink in water.

[0295] (7) Examples 10 to 12 are examples in which the amount of olefin resin used is reduced or increased compared to Example 1. In particular, in Example 10 (reduced from 40 parts by mass in Example 1 to 15 parts by mass) and Example 11 (increased from 40 parts by mass in Example 1 to 50 parts by mass), the softness, high specific gravity and wear resistance are excellent.

[0296] (8) Examples 13 and 14 are examples of increasing and decreasing the amount of softener (in Example 13, the amount used in Example 1 was reduced from 140 parts by mass to 120 parts by mass, and in Example 14, it was increased to 180 parts by mass), and the softness, high specific gravity and wear resistance are excellent.

[0297] (9) Example 8 is an example in which an olefin-based elastomer is used instead of the styrene-based elastomer of Example 4, and the flexibility, strength and abrasion resistance are excellent.

[0298] (10) Examples 15 to 20 are examples using a resin composition containing a fungicide. Compared with Example 1 in which no fungicide was used, the use of 0.1 parts or more of the fungicide suppressed the growth of mold.

[0299] 2. Preparation and evaluation of anti-slip mats

[0300] Using the resin composition for an anti-slip mat of the present invention (Example 4), injection molding was performed under the following conditions to obtain an anti-slip mat.

[0301] [Injection molding conditions for anti-slip mats]

[0302] Using the resin composition for anti-slip mats obtained in Example 4, an injection molding test was carried out under the following conditions using an injection molding machine equipped with a mold shown in Table 4 (Examples 21 to 23, Comparative Example 7). Then, injection moldability was evaluated. The results are shown in Table 4.

[0303] Injection molding machine: "IS1600DF" (model name) manufactured by Shibaura Machine Co., Ltd.

[0304] Injection molding temperature···230℃

[0305] Injection pressure···40MPa

[0306] Injection time···10sec

[0307] Mold temperature···40℃

[0308] [Table 4]

[0309]

[0310] As can be seen from Table 4, when L / t is 158.2 (Comparative Example 7), insufficient spaces filled with the resin composition are observed at the four corners of the cavity (referred to as "incomplete filling"). On the other hand, when L / t is 96.3 to 132.7 (Examples 21 to 23), the resin composition is completely filled in the mold (cavity) (referred to as "complete filling").

[0311] Next, the anti-slip mat of Example 23 obtained by injection molding was used to test the usability in a bathtub.

[0312] [Bathtub anti-slip mat test]

[0313] A bathtub (model number EXL30032) provided in a unit bathroom "サザナHBV1620UT" (trade name) manufactured by TOTO was filled with hot water at 40°C. The anti-slip mat obtained in Example 23 was placed in the bathtub, and the tester took a bath and sat down to check the touch and anti-slip effect. As a result, good touch and anti-slip effect were confirmed.

[0314] Industrial Applicability

[0315] The resin composition for anti-skid mats of the present invention has excellent A-type durometer hardness and strength and excellent wear resistance, and is suitable as a molding material for reusable anti-skid mats. In addition, when manufacturing the anti-skid mats, not only an extruder but also injection molding can be used, so the resin composition of the present invention has excellent productivity and recyclability.

[0316] Furthermore, the anti-slip mat of the present invention sinks in water by itself, so it can be fixed by its own weight in water, and it is not too heavy, so it is easy for the elderly and the like to operate.

[0317] Therefore, the anti-slip mat of the present invention can be used not only in bathrooms or bathtubs where the elderly are prone to falling, but also at the edge or bottom of a pool (swimming pool, bathtub, pool, etc.), at entrances, and at the entrances of buses, and is particularly suitable for use in bathtubs.

Claims

1. A resin composition for an anti-slip mat, characterized in that: The invention comprises synthetic barium sulfate and a thermoplastic elastomer composition as essential components, contains 20 to 70% by mass of the synthetic barium sulfate, and has a type A durometer hardness of 20 to 80. The thermoplastic elastomer composition comprises a thermoplastic elastomer component (A), an olefin resin component (B) and a softener component (C). The olefin resin component (B) is contained in a ratio of 10 to 90 parts by mass, and the softener component (C) is contained in a ratio of 100 to 300 parts by mass, relative to 100 parts by mass of the thermoplastic elastomer component (A). Regarding the volume-based particle size of the synthetic barium sulfate, the particle size of 50% of the cumulative distribution screen is 0.15 to 10 μm, the particle size of 10% of the cumulative distribution screen is 0.2 to 1 μm, and the difference between the particle size of 90% of the cumulative distribution screen and the particle size of 10% of the cumulative distribution screen is 10 μm or less. The thermoplastic elastomer component (A) is at least one selected from a styrene-based elastomer and a hydrogenated styrene-based elastomer.

2. The resin composition for an anti-slip mat according to claim 1, wherein The olefin-based resin component (B) is a polypropylene resin.

3. The resin composition for an anti-slip mat according to claim 1, wherein The softener component (C) is paraffin oil.

4. The resin composition for an anti-slip mat according to claim 1, wherein The thermoplastic elastomer composition further contains a mildew-proofing agent, and the content ratio of the mildew-proofing agent is 0.01 to 10 parts by mass based on 100 parts by mass of the thermoplastic elastomer component (A).

5. An anti-slip mat, which is a molded product of the resin composition for an anti-slip mat according to any one of claims 1 to 4, characterized in that: It contains 20 to 70% by mass of synthetic barium sulfate and has a type A durometer hardness of 20 to 80.

6. The anti-slip mat according to claim 5, wherein: The specific gravity of the molded article is greater than 1.0 and less than 2.

2.

7. The method for producing a resin composition for an anti-slip mat according to any one of claims 1 to 4, characterized in that: The process includes a mixing step using a continuous mixer.

8. The method for manufacturing the anti-slip mat according to claim 5 or 6, characterized in that: The resin composition for an anti-slip mat according to any one of claims 1 to 4 is subjected to injection molding.

Citation Information

Patent Citations

  • High filler composition

    JP1987256845A

  • Article for preventing slip under water

    JP1998215911A

  • Nonslip sheet

    JP2001181408A

  • Non-slipping elastomer composition

    JP1998279747A

  • Non-slip sheet

    JP2006291130A